Banking regulation and market making - David A. Cimon; Corey Garriott (Bank of Canada, 2017)
We present a model of market makers subject to recent banking regulations: liquidity and capital constraints in the style of Basel III and a position limit in the style of the Volcker Rule. Regulation causes market makers to reduce their intermediation by refusing principal positions. However, it can improve the bid-ask spread because it induces new market makers to enter. Since market makers intermediate less, asset prices exhibit a liquidity premium. Costs of regulation can be assessed by measuring principal positions and asset prices but not by measuring bid-ask spreads.
Keywords: G14; G20; L10; 330; Financial markets; Market structure and pricing; Financial system regulation and policies